2022
DOI: 10.1002/anie.202114619
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Catalytic C‐Glycosylation of Arenes: Expeditious Synthesis of the Remdesivir Nucleoside**

Abstract: Since early 2020, scientists have strived to find an effective solution to fight SARS‐CoV‐2, in particular by developing reliable vaccines that inhibit the spread of the disease and repurposing drugs for combatting its effects on the human body. The antiviral prodrug Remdesivir is still the most widely used therapeutic during the early stages of the infection. However, the current synthetic routes rely on the use of protecting groups, air‐sensitive reagents, and cryogenic conditions, thus impeding a cost‐effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Compared to chemical syntheses of Ψ, the one-pot rearrangement of U into Ψ reported here offers fundamental improvements in process efficiency and sustainability, which both arise from the innovative cascade reaction development. Our considerations take into account recent developments in chemo-catalytic synthesis of C-nucleosides by List and co-workers 34 , even though the application to Ψ has not been shown in their study. Besides the core features of the synthetic transformation already discussed, the absence of an isolated intermediate in the multistep reaction sequence, the avoidance of excess reagents or organic solvents used, and the consistent usage of simple process operations are important engineering characteristics of the biocatalytic process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to chemical syntheses of Ψ, the one-pot rearrangement of U into Ψ reported here offers fundamental improvements in process efficiency and sustainability, which both arise from the innovative cascade reaction development. Our considerations take into account recent developments in chemo-catalytic synthesis of C-nucleosides by List and co-workers 34 , even though the application to Ψ has not been shown in their study. Besides the core features of the synthetic transformation already discussed, the absence of an isolated intermediate in the multistep reaction sequence, the avoidance of excess reagents or organic solvents used, and the consistent usage of simple process operations are important engineering characteristics of the biocatalytic process.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical structure of the Ψ is verified by 1 H, 13 C, and 31 P-NMR (Supplementary Figs. [32][33][34][35][36][37][38] and the purity is shown as ≥99% by HPLC and assay for free phosphate.…”
Section: Scale Up Of ψ Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Meanwhile, lower yield and high cost of iodination step and complicated operation employed in the conversion from 3 to 5 compromised the value of this route. Recently, List et al reported an organocatalytic approach to this type of C-glycoside, [5] from non-halogenated compound 1. This remarkable regioselectivity on electrophile 1 indicated the pi-basicity on C-9, which is used during the halogenation of 1.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prove the synthesis effectiveness of this Co-catalyzed cyanation reaction, the cyano group can be converted into other functional groups to synthesize some important compounds, as shown in Scheme . For example, product 3ab could be used to synthesize the precursors of the unnatural nucleobase fragment seen in Remdesivir, a marketed drug licensed for the treatment of COVID-19, and compared it with the route in the literature, and the experimental results are shown in the SI for details. This structural motif is also present in a variety of other approved and experimental drugs …”
mentioning
confidence: 99%